Psychological help in oncology practice - Mukharovska, Inna (Psychosomatic Medicine and General Practice, 2017)
Background. The psychological effects of cancer and its treatment on the patients, their families, and healthcare workers point the need to develop a program of psychological interventions for use in oncology practice. Methods. The study was conducted at the Kyiv City Clinical Cancer Center during 2014-2016 years and had an observational design. It included 422 cancer patients: 80 patients – diagnostic stage, 187 - primary treatment and 155 - secondary treatment caused by cancer progression; 218 family members: 79 – relatives of patients on primary treatment (Gp), 68 - secondary treatment (Gs), 71 - palliative care (Gpal). In the study also participated 50 oncologists. We used Hospital Anxiety and Depression Scale (HADS), Big Five Personality Questionnaire (5PFQ), Dealing with Difficult Life Situations (developed by W. Janke, H. Erdmann), Type Attitude to the Disease Questionnaire (TOBOL), Quality of Life Index (developed by J. E. Mezzich, N. Cohen, J. Liu, M. Ruiperez, and G. Yoon). Oncologists were evaluated for emotional burnout symptoms by Maslach Burnout Inventory. Results. Cancer has caused a significant influence on patients’ mental state, reflected in personal, behavioral and psychosocial levels. HADS showed more pronounced anxious versus depressive symptoms (p<0.05), although the symptomatic structure among different patients was similar. On diagnostic stage, depression and anxiety were higher (p<0.05). In patients were noted destructive personal patterns (12,7%), ineffective coping strategies (24,6%), maladjusted reactions on disease (62,8%). The main types of reactions on the disease were: anosognostic (13,0%), anxious-sensitive (11,4%), ergopathic-anxious (10,4%), sensitive (7,8%), anxious (7,6%) and hypochondriac (6,4%). Patient`s relatives experienced high levels of stress due to cancer diagnosis. The high levels of distress were noted in 92,4% relatives - in Gp, 86,8% - Gs and 91,5% - Gpal. Emotional exhaustion in oncologists was estimated at 16,1 ± 9,1, depersonalization - 6,0 ± 4,5 points, professional achievements - 35,4 ± 7,5 points. In 34% oncologist from 1 to 3 components of burnout were present. Conclusion. According to the results, psychological help is a major component of cancer management. Due to high levels of distress and emotional burnout, it must be provided not only to patients but to their relatives (caregivers) and oncologists. The results of this study could help in the creation of a new complex program of psychological interventions for these individuals.